2016
DOI: 10.1111/bju.13718
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose desmopressin combined with serum sodium monitoring can prevent clinically significant hyponatraemia in patients treated for nocturia

Abstract: The incidence of hyponatraemia can be reduced by using minimum effective gender-specific dosing with the ODT formulation of desmopressin (25 μg in women, 50 μg in men). A sodium monitoring plan is proposed whereby baseline sodium must be ≥135 mmol/L (especially important in the elderly), with additional monitoring at week 1 and month 1 for those at elevated risk because they are aged ≥65 years or receiving concomitant medication associated with hyponatraemia. This monitoring plan would help to prevent some at-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…Patients with nocturia have to face many hurdles before being diagnosed properly and treated with desmopressin, instead of OAB/BPO medication . Potential reasons for this, besides side effects, are the limited knowledge of clinicians regarding the drug and how to use it, and anxiety about safety, regardless of the evidence that with the available low‐dose formulations, hyponatremia is extremely rare, even in older patients . There is a clear need for a summary of the available information and a simple algorithm on how desmopressin should be used in adults with nocturia.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with nocturia have to face many hurdles before being diagnosed properly and treated with desmopressin, instead of OAB/BPO medication . Potential reasons for this, besides side effects, are the limited knowledge of clinicians regarding the drug and how to use it, and anxiety about safety, regardless of the evidence that with the available low‐dose formulations, hyponatremia is extremely rare, even in older patients . There is a clear need for a summary of the available information and a simple algorithm on how desmopressin should be used in adults with nocturia.…”
Section: Introductionmentioning
confidence: 99%
“…38,40 It is important to remain aware that hyponatremia is a notable side effect of desmopressin therapy, as well, particularly in patients 65 years or older. 46 The risk of hyponatremia is 8% in patients over 65 compared with 1% in younger patients. 47 Individual countries have licensed varying preparations of desmopressin listed herein.…”
Section: Choi Ce Of Tre Atmentmentioning
confidence: 99%
“…This phenomenon is explained by larger expression of V2 receptors for vasopressin [ 23 ]. For this reason, following the results of numerous clinical studies evaluating therapeutic and adverse effects (in this case especially the risk of hyponatremia), it was found that the recommended daily therapeutic dose for women was 25 µg and for men 50 µg desmopressin lyophilisate, administered sublingually 1 hour before bedtime [ 24 , 25 , 26 ]. In the above studies, subjects receiving desmopressin reported, in comparison to the placebo patients, a significant improvement in the number of nocturia episodes, and also the secondary endpoints, which included an assessment of the overall quality of life and sleep.…”
Section: Desmopressin In the Treatment Of Nocturnal Polyuriamentioning
confidence: 99%